LINGUISTIC MECHANISMS AND RHETORICAL TOOLS OF MANIPULATION IN POLITICAL TEXTS - Sarsenova Ulbosin Bazarbay kizi,Mamatkulova Saida Shukurjonovna (International Journal of Literature and Language Studies, 2026)
This article explores the linguistic mechanisms and rhetorical tools of manipulation within political discourse, with a specific focus on the challenges they present in translation. Drawing upon the critical discourse analysis frameworks of Charteris-Black, Van Dijk, and Fairclough, the study examines four primary manipulative instruments: conceptual metaphors, euphemisms and dysphemisms, lexical repetition, and syntactic structures. The analysis reveals that these tools function as "linguistic camouflage" to shape public perception, establish ideological polarization, and reinforce institutional power. Furthermore, the article evaluates the ideological dilemmas faced by translators when navigating these manipulative structures. It contrasts key translation strategies, including pragmatic adaptation, domestication, and foreignization, emphasizing that the translation of political texts is never neutral. The study concludes that uncovering hidden meanings and preserving the source text's persuasive intent requires critical awareness, as every translation choice either challenges or reinforces the embedded power dynamics.